An Application of Psychological Reactance Theory to College Student Voter Registration and Mobilization. Issue 3 (2nd October 2022) - Reynolds-Tylus, Tobias; Schill, Dan
ABSTRACT: The purpose of this study was to test political engagement messages (voter registration and voter mobilization) effectiveness with younger adults using psychological reactance theory as a guiding framework. Two online survey experiments using a 2 (message frame: gain- vs. loss-frame) X 2 (social norm: positive vs. negative) factorial design found that in the context of voter registration, consistent with prior research, both a loss-framed message and a positive norm message elicited greater freedom threat and reactance. However, these findings were not replicated in the context of voter mobilization. Across both topics, the arousal of reactance was associated with diminished behavioral intention (either for registering to vote or for voting). While the social norms approach has been found effective in mobilization campaigns, findings from this study demonstrate that an implicit threat to one's freedom (in the form of a positive social norms message) can elicit reactance among non-registered voters. This research suggests that political marketers should be aware of the potential for reactance to messages promoting voter registration among non-registered voters and be aware of potential backlash effects of loss-framed and positive norm-based messages in voter registration communication.